2003
DOI: 10.3758/bf03196508
|View full text |Cite
|
Sign up to set email alerts
|

Compared to what? Effects of categorization on hedonic contrast

Abstract: Test stimuli are rated less "good" following very good context stimuli than when presented either alone or following neutral context stimuli. This diminution in rating is called hedonic contrast. In two experiments, the degree of hedonic contrast depended on how subjects were instructed to categorize context and test stimuli. Contrast was substantially attenuated if context and test stimuli were said to belong to different categories. The effect was demonstrated for beverages (Experiment 1) and birds (Experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
82
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(90 citation statements)
references
References 24 publications
5
82
2
Order By: Relevance
“…This prediction was based on the demonstration of similarity based contextual recruitment for contrast effects in the literature (Parducci et al, 1976;Sarris, 1976;Zellner et al, 2003). This prediction was largely borne out by the results of Experiment 3.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…This prediction was based on the demonstration of similarity based contextual recruitment for contrast effects in the literature (Parducci et al, 1976;Sarris, 1976;Zellner et al, 2003). This prediction was largely borne out by the results of Experiment 3.…”
Section: Discussionmentioning
confidence: 89%
“…For example, Brown (1953) found that evaluations of lifted weights were unaffected by having participants lift other objects not associated with the experimental stimuli (such as a tray). A number of researchers have demonstrated diminished effects of context as a function of the perceived similarity of contextual and target stimuli, as determined by categorical classification, relevance to the task, or magnitude differences (Sarris, 1976;Zellner et al, 2003). For example, Parducci, Knoble, and Thomas (1976) found that context effects on judgments of square sizes were largely independent of the manipulation of circle sizes and vice versa, implying that squares recruited other square sizes for contextual comparison and circles recruited other circle sizes for contextual comparisons.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We know that hedonic contrast can be demonstrated not only when the comparison group (Group N in Experiment 1) sees no context stimuli at all, but also when the comparison group sees context stimuli hedonically equivalent to the test stimuli (Zellner et al, 2003). So in Experiment 3, some subjects saw unattractive context paintings (as did Group C in Experiment 2), and others saw just as many context paintings, similar in hedonic value to the test paintings.…”
Section: Methodsmentioning
confidence: 99%
“…When positive context stimuli are presented before a set of more hedonically neutral test stimuli, both negative hedoni c contrast (Parker, Bascom, Rabinovitz, & Zellner, 2008;Rota & Zellner, 2007;Zellner, Rohm, Bassetti, & Parker, 2003) and a decrease in preference between test stimuli (i.e., hedonic condensation) occur (Zellner, Allen, Henley, & Parker, 2006;Zellner, Mattingly, & Parker, 2009). So negative hedonic contrast and hedonic condensation cooccur when good stimuli precede less good stimuli.…”
mentioning
confidence: 99%